Presence of Bromotyrosine Alkaloids in Marine Sponges Is Independent of Metabolomic and Microbiome Architectures - Ipsita Mohanty (American Society for Microbiology, 2021)
ABSTRACT Marine sponge holobionts are prolific sources of natural products. One of the most geographically widespread classes of sponge-derived natural products is the bromotyrosine alkaloids. A distinguishing feature of bromotyrosine alkaloids is that they are present in phylogenetically disparate sponges. In this study, using sponge specimens collected from Guam, the Solomon Islands, the Florida Keys, and Puerto Rico, we queried whether the presence of bromotyrosine alkaloids potentiates metabolomic and microbiome conservation among geographically distant and phylogenetically different marine sponges. A multi-omic characterization of sponge holobionts revealed vastly different metabolomic and microbiome architectures among different bromotyrosine alkaloid-harboring sponges. However, we find statistically significant correlations between the microbiomes and metabolomes, signifying that the microbiome plays an important role in shaping the overall metabolome, even in low-microbial-abundance sponges. Molecules mined from the polar metabolomes of these sponges revealed conservation of biosynthetic logic between bromotyrosine alkaloids and brominated pyrrole-imidazole alkaloids, another class of marine sponge-derived natural products. In light of prior findings postulating the sponge host itself to be the biosynthetic source of bromotyrosine alkaloids, our data now set the stage for investigating the causal relationships that dictate the microbiome-metabolome interconnectedness for marine sponges in which the microbiome may not contribute to natural product biogenesis. IMPORTANCE Our work demonstrates that phylogenetically and geographically distant sponges with very different microbiomes can harbor natural product chemical classes that are united in their core chemical structures and biosynthetic logic. Furthermore, we show that independent of geographical dispersion, natural product chemistry, and microbial abundance, overall sponge metabolomes tightly correlate with their microbiomes.